Justice and Mercy in the «Divine Comedy» - Cortés Pacheco, Carmen (Pensamiento. Revista de Investigación e Información Filosófica, 2024)
The eternal question of justice occupies a central place in the worldview that Dante expresses allegorically and iconically in the Divine Comedy. We find it as an attribute of God who gives to each one according to his merits, but whose Love moves him to pity men, because the justice of human actions cannot reach the Creator according to equality, nor can it restore all that the human receives from Him and owes to Him. Justice is also present in all the circles that Dante’s pilgrimage passes through. This gives reasons for the state of those souls he encounters, not only in hell, but also in purgatory, in limbo and in paradise. A global analysis of Dantian justice brings to light the profound imprint of the Christian theological-biblical tradition, of classical philosophy —especially Aristotelian—, as well as the synthesis of both in the legacy of Saint Thomas Aquinas. Dante emphasises Aquinas among the wise men of the Paradise —thus anticipating the opinion of the Church a few years later. Dante Alighieri assumes the philosophical-moral magisterium of St. Thomas and this is very evident in the Dantian conception of justice.